2013
DOI: 10.1002/grl.50729
|View full text |Cite
|
Sign up to set email alerts
|

Two distinct roles of Atlantic SSTs in ENSO variability: North Tropical Atlantic SST and Atlantic Niño

Abstract: Two distinct roles of the Atlantic sea surface temperatures (SSTs), namely, the North Tropical Atlantic (NTA) SST and the Atlantic Niño, on the El Niño-Southern Oscillation (ENSO) variability are investigated using the observational data from 1980 to 2010 and coupled model experiments. It appears that the NTA SST and the Atlantic Niño can be used as two independent predictors for predicting the development of ENSO events in the following season. Furthermore, they are likely to be linked to different types of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
111
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(128 citation statements)
references
References 36 publications
10
111
1
Order By: Relevance
“…Similar to [14,15] [14,15]. For ATL_VAR, the response is stronger compared to the response to the Atlantic Niño, and comparable in magnitude to the observed response.…”
Section: North Tropical Atlantic-pacific Teleconnectionsupporting
confidence: 62%
See 3 more Smart Citations
“…Similar to [14,15] [14,15]. For ATL_VAR, the response is stronger compared to the response to the Atlantic Niño, and comparable in magnitude to the observed response.…”
Section: North Tropical Atlantic-pacific Teleconnectionsupporting
confidence: 62%
“…For ATL_VAR, the response is stronger compared to the response to the Atlantic Niño, and comparable in magnitude to the observed response. However, there is no indication of the response to the NTA being more central Pacific ENSO events compared to the response to the ATL3 as suggested by [14,15], either in observations or the model results. It is possible that that results depend on the exact period analyzed.…”
Section: North Tropical Atlantic-pacific Teleconnectionmentioning
confidence: 79%
See 2 more Smart Citations
“…The influence of the Atlantic Ocean appears to be small, although it has been suggested that SST anomalies in the north tropical Atlantic during boreal spring can affect ENSO occurrence (Ham et al 2013). The Indian Ocean (IO) variability was long thought to be a passive response to ENSO (Latif and Barnett 1995), but later studies have suggested that the IO evolves to some degree independently of ENSO (Saji et al 1999;Webster et al 1999).…”
Section: Introductionmentioning
confidence: 99%